Audit Komunikasi Program Roadshow Launching Layanan 5G Telkomsel Di Solo - Dorina Athalia; Alivia Noer; Rahmadani Arofia; Vanessa Chastity; Amanda Wynona (Universitas Swadaya Gunung Jati, 2022)
This study aims to discover the effectivity of Telkom Corporation's roadshow program and its corporate communication's strategy to introduce the new 5G feature towards the society in Solo. With a descriptive qualitative approach, there are two datas gathered for the study. The first data is the primary data gained from an interview with one of Telkom's corporate communication's officer and a forum group discussuon with some informants. And the secondary data gained from collecting literatures through various sources to support the primary data. The interview with one of the corporate communication's officer presents a result of their internal evaluation which stated that the roadshow program to launch 5G service in Solo was effective, given the media coverage upon its program was heard in Medan. However, the analysis done by the researchers showed a contradictive result, which stated that the program was ineffective. Telkomsel's roadshow program to launch 5G service wasn't quiet significant to trigger society's awareness towards the new 5G feature.